Performance, nutrient digestibilities, and metabolic profiles of Holstein calves fed whole milk or milk replacer at 2 feeding levels - T. Chapelain; J.N. Wilms; J. Martín-Tereso; L.N. Leal; J.B. Daniel (Journal of Dairy Science, 2025)
ABSTRACT: The macronutrient composition of common milk replacers (MR) largely differs from bovine whole milk (WM). These differences are more nutritionally relevant when calves receive higher milk allowances. Therefore, the present study compared fresh WM with a conventional MR fed at 2 level of feeding allowances evaluating growth performance, apparent total-tract nutrient digestibilities, N balance, and serum metabolite profiles in calves. Newborn male Holstein calves (n = 48; 1.96 ± 0.99 d of age; 45.0 ± 4.37 kg BW) were blocked by arrival date and age. Calves in each block were then randomly assigned to the 4 treatments (n = 12 per treatment): MR or WM at a high (9.0 L/d) or low feeding allowance (4.5 L/d) fed 3 times daily. Calves were weaned between wk 6 and 10 following the introduction of the starter feed in wk 6. The study ended 13 wk after the arrival at the facility. Blood and body weights were collected on arrival, and weekly thereafter. Total 24h-collection periods of feces and urine was performed at wk 2, 4, 5, 7, 9, 11, and 13. Remarkably, no interactions were observed between liquid feed and level of supply. Calves fed MR had higher ADG during the preweaning phase than to calves fed WM. However, calves fed WM had an increased growth rate postweaning, resulting in no difference in BW at the end of the study. Calves fed WM had a higher apparent crude fat digestibility during the weaning period. Metabolic N efficiency, expressed as N balance relative to digestible N supply, was higher during the preweaning phase, but tended to be lower during the postweaning phase for calves fed MR as compared with calves fed WM. In the preweaning period, serum glucose, BHB, nonesterified fatty acids (NEFA), total protein (TP), urea, albumin, globulin, triglyceride (TG), and cholesterol were influenced by liquid feed source. Carryover effects of milk source on TG and TP were observed during the postweaning period. As expected, calves fed a high milk allowance showed better ADG at preweaning and were consistently heavier throughout the study than calves fed a low milk allowance. Feeding a high milk allowance did not negatively affect nutrient digestibility during the postweaning phase. In the preweaning phase, milk allowance affected glucose and cholesterol metabolism, whereas TG, TP, albumin, and NEFA concentrations were affected during the postweaning period. From a single oral dose of indigestible markers (Cr-EDTA, lactulose, and d-mannitol), calves fed a high milk allowance showed greater urinary recovery of all markers after 6 h of collection, but not after 24 h. Calves fed a high milk allowance had a higher proportion of days with lower fecal scores during the preweaning phase. In conclusion, the serum metabolite profiles of calves throughout the study were highly influenced by milk source. Higher milk allowance increased growth performance and had no adverse effects on starter feed intake or nutrient digestibility in the postweaning phase. The multiple effects described for milk source and level of supply were overall independent, presenting no relevant interactions.